2022
DOI: 10.3389/fpls.2022.1047294
|View full text |Cite
|
Sign up to set email alerts
|

Forage quality and physiological performance of mowed alfalfa (Medicago sativa L.) subjected to combined light quality and drought

Abstract: Alfalfa (Medicago sativa) can dwell in water-deficient habitats, where it is difficult to predict dry mass (DM) production and forage quality due to understory transmittance. Mowing is a recommended practice for alfalfa populations under drought, but its effect on forested land receives less attention. In a controlled indoor experiment, we found that drought better reduces shoot DM weight and crude fiber content (CFi) in blue light (33.7% red, 48.5% green, and 17.8% blue lights) than red light (71.7% red, 13.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 64 publications
3
12
0
Order By: Relevance
“…Chitosan oligosaccharide (CO) can be widely obtained from seafood wastes and used as a plant-growth regulator. The direct addition of CO can increase drought assistance by controlling stomatal conductance in Buddhist pine ( Podocarpus macrophyllus ) seedlings [ 52 ]. The CO addition can also improve the ability of nutrient uptake and utilization in Buddhist pine [ 29 , 51 ] and fragrant rosewood ( Dalbergia odorifera ) seedlings [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan oligosaccharide (CO) can be widely obtained from seafood wastes and used as a plant-growth regulator. The direct addition of CO can increase drought assistance by controlling stomatal conductance in Buddhist pine ( Podocarpus macrophyllus ) seedlings [ 52 ]. The CO addition can also improve the ability of nutrient uptake and utilization in Buddhist pine [ 29 , 51 ] and fragrant rosewood ( Dalbergia odorifera ) seedlings [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although alfalfa is highly drought tolerant, it requires a large amount of water for growth; thus, cultivation in arid and semi-arid areas is overly dependent on irrigation, and the growth process is susceptible to drought stress ( Attram et al., 2016 ). The growth indicators of alfalfa, such as stem length, stem thickness, number of tillers, and leaf area, decrease after being subjected to drought stress ( He et al., 2022 ). Alfalfa growth and physiological characteristics can also be limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, perennial roots reserve essential substances that can support and fuel annual shoot sprouting. Mowing has been proven to be a feasible practice that can promote annual sprouting from perennial roots help the plants to cope with the shock of drought’s effects [ 19 , 20 ]. Mowing forage plants can improve their water-use efficiency through modulating stomatal conductance and gas exchange [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mowing has been proven to be a feasible practice that can promote annual sprouting from perennial roots help the plants to cope with the shock of drought’s effects [ 19 , 20 ]. Mowing forage plants can improve their water-use efficiency through modulating stomatal conductance and gas exchange [ 19 ]. It has been identified that mowing can increase the synthesis and accumulation of secondary metabolites in annual shoots of medicinal plants [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation